Pengembangan Teknik Cerdas Cermat Kimia Berbasis HOTS dalam Model Team Games Tournament untuk Meningkatkan Motivasi Belajar dan Keterampilan Berpikir Kritis Peserta Didik - Ningsi, Surya; Gani, Tabrani; Auliah, Army (Chemistry Education Review (CER), 2020)
The use of appropriate techniques will determine the success of achieving student competencies in learning. Learning techniques that tend to be monotonous make students less actively involved in learning and less training students’ critical thinking skills. Development of chemistry quiz technique based on HOTS in TGT Model is expected to be implemented effectively in class and assist students in learning chemistry. This development research aims at discovering: (1) the description of the development of chemistry quiz technique based on HOTS in TGT Model; and (2) the extent of the quality of chemistry quiz technique based on HOTS in TGT Model to enhance learning motivation and critical thinking skills of students on Atomic Structure material. The study consists of several stages, namely analysis, design, development, implementation, and evaluation. The product developed was test to 35 students of grade X MIA 4 at SMAN 3 Bone of Academic Year 2019/2020. The validity of the product was test by two assessors. This study employed the stages of TGT model, namely class presentation, group work, games, tournament, and appreciation. The stages of chemistry quiz was started from association activity and presented in a form of a quiz or question which used HOTS questions along with the games to motivate the students in learning and think critically. The results of the study reveal that: (1) the mean score of product validity is 3.71 (very valid); (2) the data of learning motivation questionnaire X ̅ = 3.31 (high); (3) the mean score of N-Gain of KBK is 0.79 (high); (4) The teacher and students indicated a very positive response with the percentage of 96.88% and 87.11%. Therefore, the conclusion is the chemistry quiz technique based on HOTS in TGT Model developed in chemistry learning on Atomic Structure material is valid, practical, and effective to enhance learning motivation and critical thinking skills of students.